Fractional Order Darwinian Particle Swarm Optimization - Couceiro, Micael S. (2019)
The Darwinian Particle Swarm Optimization (DPSO) is an evolutionary algorithm that extends the Particle Swarm Optimization (PSO) using natural selection, or survival-of-the-fittest, to enhance the ability to escape from local optima. This paper presents a method for controlling the convergence rate of the DPSO using fractional calculus (FC) concepts. The fractional order (FO) DPSO, denoted as FO-DPSO, is tested using several well-known functions and the relationship between the fractional order velocity and the convergence of the algorithm is observed.